Pengaruh Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia 2019-2023 - Salsabila, Salsabila; Lusiana, Lusiana; Sari, Silvia (ARZUSIN, 2025)
This study aims to determine how much influence the capital structure and company size have on the company's value with profitability as an intervening variable in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023. This study uses a quantitative research type with sampling using the purposive sampling method. The population in this study amounted to 95 companies. while the sample taken was 26 companies that had met the criteria. The method used in this study is descriptive statistical analysis and multiple linear regression analysis with the help of the SPSS version 26 program. The results of this study obtained based on partial tests (t-tests) obtained: (1) Capital structure does not have a significant effect on profitability, (2) Company size does not have a significant effect on profitability, (3) Capital structure has a significant effect on company value, (4) Company size does not have a significant effect on value, (5) Profitability has a significant effect on company value, (6) Capital structure does not have a significant effect on company value through profitability as an intervening variable, (7) Company size has a significant effect on company value through profitability as an intervening variable.